Metal‐Free Synthesis of S‐Aryldithiocarbamates: Aryl C−S Bond Formation at Room Temperature†. Issue 28 (22nd July 2022) - Madassery, Geo Paul; M, Vageesh; Panja, Subir; P, Hima; Dey, Raju
Abstract: Aryl halides containing electron‐withdrawing substituent(s) at ortho and para position undergoes aromatic nucleophilic substitution reaction with sulfur nucleophile present in dithiocarbamate anions at room temperature. In the present study, several cyclic and acyclic secondary amines reacted in situ with carbon disulfide to form dithiocarbamate anions, which then react with different haloarenes resulting in the formation of aryldithiocarbamates. A series of aryldithiocarbamates are obtained in high yields by this procedure. Abstract : An efficient one‐pot condensation of amine, carbon disulfide and aryl halides in DMF at room temperature provides S‐aryldithiocarbamates with good to excellent yields. A wide range of cyclic and acyclic amine underwent this reaction to provide easy access to a library of aryldithiocarbamates. The simple reaction strategy, high yields of products, and no requirement of transition metal catalyst make this procedure more attractive.